Think : the life of the mind and the love of God - Piper, John, 1946- (Wheaton, Ill. : Crossway, 2010)
Piper urges us to think for the glory of God. He demonstrates from Scripture that glorifying God with our minds and hearts is not either-or, but both-and. Thinking carefully about God fuels passion and affections for God. Likewise, Christ-exalting emotion leads to disciplined thinking. --from publisher description
Foreword / Mark A. Noll -- My pilgrimage -- Deep help from a dead friend -- Reading as thinking -- Mental adultery is no escape -- Rational gospel, spiritual light -- Love for God : treasuring God with all your mind -- Jesus meets the relativists -- The immorality of relativism -- Unhelpful anti-intellectual impulses in our history -- You have hidden these things from the wise and understanding -- In the wisdom of God the world did not know God through wisdom -- The knowledge that loves -- All scholarship for the love of God and man -- A final plea.
Includes bibliographical references and indexes.
Keywords: Thought and thinking -- Religious aspects -- Christianity; Learning and scholarship -- Religious aspects -- Christianity